Integrated scheduled waste management system in Kuala Lumpur using expert system - Kabbashi, Nassereldeen Ahmed; Jami, Mohammed Saedi; Jazzar, Munif A.; Md Azman, Nur Adibah (Academic Journals, 2011)
Over the past decade, Malaysia has enjoyed tremendous growth in its economy. This has brought about a population growth together with a great influx of foreign workforce to the cities. This resulted in an increase in the amount of scheduled waste generated. Furthermore, scheduled waste management has long been a problem for local authorities in Kuala Lumpur. Continued illegal dumping by waste generators is being practiced at large scale due to lack of proper guidance and awareness. This report reviewed and discussed service provided for scheduled waste management by an authority and international scenario of scheduled waste management. An expert system was developed to integrate scheduled waste management in Kuala Lumpur. The knowledge base was acquired through journals, books, magazines, annual report and web sites. An object oriented expert system shell, Microsoft Visual Basic 2005 Express Edition was used as the building tool for the prototype development. The overall development of this project was carried out in several phases which are problem identification, problem statement, literature review, identification of domain experts, prototype development, knowledge acquisition, knowledge representation and prototype development. Scheduled waste expert system is developed based on five types of scheduled waste management which are label requirements, packaging requirements, impact of scheduled wastes, recycling of scheduled wastes and recommendations. Besides, it contains several sub-modules by which the user can obtain a comprehensive background of the domain. The output is to support effective integrated scheduled waste management.